Back and forth: labor market vulnerability and exclusion among mexicans in the United States and return migrants in Mexico in a changing demographic and migratory context - Bautista Leon, Andrea (Geografares, 2017)
The current scenario of the migration between Mexico and the United States has characteristics never seen before. A decelerating migratory flow towards the north and an unexpected return of Mexicans to their communities of origin. At the same time and without taking into account the facts, immigration policy and governmental speech intensify the control of the border and manifests the need to expel a large number of undocumented Mexicans. In this article, I analyze the demographic trends of the workforce under a binational and longitudinal perspective through the construction of a semi-panel. The results show convergent trends in both populations towards a gradual aging, the concentration of Mexicans in the United States at young adult ages and the return of Mexicans in all age groups to the labor market. It also shows the persistent segmentation of the U.S. labor market and the vulnerability regarding unemployment that returnees face in Mexico. Keywords: Mexico-United States Migration; Return Migration; Labor Market.